GEMINASI DALAM DIALEK MELAYU SAMBAS - Firman Susilo (Balai Bahasa Provinsi Riau, 2014)
Malay Sambas Dialect (DMS) is still spoken by a community of native speakers who live and thrive in Sambas district and surrounding area in the province of Kalimantan Barat. DMS, which became part of the language/regional dialects in Indonesia, is used as a lingua franca and the language of culture, which function as a mean of communication among members of society, as well as other mean to preserve culture such as ritual tradition and folklore.This paper described about gemination in the DMS. The results of this research can be used as material description and comparative assessment of the relationship between the languages, and can also be used as consideration to construct a grammar and dictionary of Malay dialect Sambas. Dialek Melayu Sambas (DMS) masih dituturkan oleh masyarakat penuturnya yang hidup dan berkembang pada wilayah Kabupaten Sambas dan sekitarnya di Provinsi Kalimantan Barat. DMS, yang menjadi bagian dari bahasa/dialek daerah yang ada di Indonesia ini, dipergunakan sebagai bahasa pergaulan dan bahasa kebudayaan, yang artinya selain sebagai sarana komunikasi antaranggota masyarakat, juga sebagai sarana untuk memelihara kebudayaan lainnya, seperti upacara adat dan cerita rakyat. Dalam tulisan ini dideskripsikan tentang geminasi dalam DMS tersebut. Hasil pendeskripsian dapat dijadikan bahan pengkajian hubungan dan perbandingan antarbahasa, serta dapat pula dijadikan sebagai bahan pertimbangan untuk menyusun tata bahasa dan kamus dialek Melayu Sambas.